The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2017
DOI: 10.22161/ijeab/2.5.17
|View full text |Cite
|
Sign up to set email alerts
|

Callus induction and plant regeneration via leaf segments of three accessions of African rice (Oryza glaberrimaStued.)

Abstract: Abstract-

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 7 publications
0
3
0
Order By: Relevance
“…Highly significant mean squares were noted for parameters which define tissue culture response over rice genotypes. Differential genotype response for callus induction has been reported by Diawuoh et al, (2016).…”
Section: Callus Initiationmentioning
confidence: 88%
See 1 more Smart Citation
“…Highly significant mean squares were noted for parameters which define tissue culture response over rice genotypes. Differential genotype response for callus induction has been reported by Diawuoh et al, (2016).…”
Section: Callus Initiationmentioning
confidence: 88%
“…Different concentrations of 2,4-D havebeen assessed by different workers to find the optimal working concentration that gives best callus induction. A study conducted by Vennapusa et al, (2015) showed that highest callus frequency was obtained on LS media containing 2.5 mg/L 2,4-D. Diawuoh et al, (2016) also worked with dehusked rice and reported that 2,4-D is the best auxin for callus induction.…”
Section: Callus Initiationmentioning
confidence: 99%
“…This could be attributable to a lack of concern or interest in genetic manipulation, possibly due to the absence of the appropriate in vitro regeneration protocols for local cultivars. 20 , 21 In fact, difficulties in the transformation and regeneration of African local cultivars, such as O. glaberrima , have been reported in several studies. 20–23 …”
Section: Introductionmentioning
confidence: 99%